'It's a funny thing that they were all bad men': cultural conflict and integrated tourism policy in Shetland, UK. (1st January 2011) - Grydehøj, Adam
The municipal authority of Shetland (Scotland) uses tourism promotion as a carrier for holistic brand messages and as a tool of paradiplomacy. This comes into conflict with Shetland's local identity concept, which discourages community engagement with certain types of tourism and heritage development and clashes with the tourism promotion's wider aim attracting immigrants. Although the increasing sophistication of place branding offers genuine opportunities for sub-national island jurisdictions in particular, concerns can be raised regarding the effectiveness and appropriateness of moving tourism promotion too far in the direction of paradiplomacy without real focus on the desires of the local community.